ANALISIS IMPLEMENTASI PERMAINAN ORIGAMI DALAM MENGEMBANGKAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI KOBER AL HIDAYAH - Susanti, Susi; Pusvitasari, Devina Adinda; Hidayat, Yusuf (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
One of the efforts to improve early childhood’s aged 5-6 years fine motor skill can be carried out through origami game. This study aims to find out the implementation of origami game, obstacles, and solutions for the implementation of origami game to develop early childhood’s aged 5-6 years fine motor skill in Kober Al Hidayah. In this study, the researchers employ a qualitative approach under a phenomenological method. The results of the study show that the implementation of origami game run well which could assist to develop early childhood’s aged 5-6 years fine motor skill at Kober Al Hidayah. Furthermore, there are obstacles in the implementation of origami game, such as some early childhoods still have difficulties to produce an origami result from paper independently. To overcome the difficulties, a drilling technique is used combined with a mentoring strategy and rewards in the form of praise and giving stars. As a result, the use of drilling techniques, mentoring strategies, and providing rewards can be a solution to overcome the difficulties faced by some early childhoods. In conclusion, origami game combined with drilling techniques and accompanied by teachers diligently, besides given rewards in the form of praise and giving stars can assist to develop early childhood’s aged 5-6 years fine motor skill at Kober Al Hidayah.